2018
DOI: 10.1002/lary.27688
|View full text |Cite
|
Sign up to set email alerts
|

Safety of outpatient unilateral medialization laryngoplasty across two academic institutions

Abstract: Objectives/Hypothesis: Unilateral ML is a commonly performed surgery for dysphonia secondary to glottic insufficiency. The safety of this procedure performed in the outpatient setting has not been extensively examined. The purpose of the study was to assess the safety of outpatient unilateral ML in adults and determine the incidence and timing of postoperative complications across two tertiary-care academic medical centers.Study Design: Retrospective chart review, Methods: A review of patients undergoing unila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The reported complication rate for patients undergoing type 1 thyroplasty is between 7% and 20%. 12,13,15,17,18,[19][20][21][22] However, our study found a major complication rate of 5.6% with no long-term morbidity or mortalities. There were 4 cases of airway complications that were considered major; however, none of the patients required intubation or tracheostomy.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The reported complication rate for patients undergoing type 1 thyroplasty is between 7% and 20%. 12,13,15,17,18,[19][20][21][22] However, our study found a major complication rate of 5.6% with no long-term morbidity or mortalities. There were 4 cases of airway complications that were considered major; however, none of the patients required intubation or tracheostomy.…”
Section: Discussionmentioning
confidence: 73%
“…These data fit well with other published reports. Of the 214 patients who underwent outpatient type 1 thyroplasty in studies published by Chau et al, 19 Junlapan et al, 15 Cotter et al, 13 Zhao et al, 20 and Bray et al, 18 there were no obstructive hematomas or need for intubation or surgical airway intervention in the acute postoperative period. The only complications of nonobstructive hematoma and implant extrusion occurred in patients on anticoagulation and in patients with poor implant placement or prior radiation therapy, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies promote risk stratification to determine, which patients may be discharged safely, and which may be at a higher risk for complications or potential readmissions requiring overnight observation. 12,14,18,19 In our study, with a large number of patients, we observed that 4.9% of patients suffered an adverse event within 30 days following surgery, with a readmission rate of 2.1% (at days 2, 5, 7, 9, 10, and 17), a reoperation rate of 1.8% (at days 0, 0, 1, 6, and 20) and a 30-day mortality rate of 1.4%. There were two patients who underwent unplanned reintubations.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,10 The more serious complications are thought to be seen more frequently in AA. 7,11 While recent studies have demonstrated that LFS is safe to be performed as an outpatient procedure due to a low percentage of patients with immediate complications, [12][13][14] risk factors leading to admission or increased complication rates remain undetermined. Identification of these risk factors for complications may help better target postoperative observation to select patients undergoing LFS.…”
Section: Introductionmentioning
confidence: 99%